Regional features of development of retail in the Republic of Belarus - Sheleg, Nikalay S.; Belakhvost, Pavel L. (Journal of the Belarusian State University. Geography and Geology, 2019)
A geographical analysis of the distribution of trade networks in the administrative districts of Belarus is given in the article. An assessment of the attractiveness of the regions of the country for retailers, incl. retail trade. The geographical structure of the largest retail trade network has been revealed. The dominance of individual retail chains in the segments of the sale of goods was determined. It has been established that the most developed regions in terms of trade are the largest cities and districts in terms of population and turnover. The modern trend of geographical expansion of trade networks in small and medium-sized regions of Belarus was noted. On an example of the largest trading networks the diffusion of expansion of trading territories is shown. The conclusion is drawn that, given the existing territorial structure, the development of new trade networks in most regions of the country is currently difficult and limited.